KAJIAN LITERATUR PERAN GURU DALAM MENINGKATKAN KEMAMPUAN LITERASI SISWA SEKOLAH DASAR - Tri Purwati; Chairunissa, Chairunissa; Okke Rosmaladewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine in depth the importance of teachers' roles in improving elementary school students' literacy skills through a literature review approach. Literacy is a fundamental and essential core competency in supporting student learning success. The method used is a literature review, reviewing various scientific sources, such as journals and relevant previous research. The results of the study indicate that teachers play a strategic role as facilitators, motivators, mediators, and innovators in literacy learning. Teachers who are able to plan engaging lessons, use appropriate strategies, and create a conducive literacy environment can improve students' reading, writing, and critical thinking skills. Therefore, improving teachers' pedagogical competence is a crucial factor in developing elementary school students' literacy.